Vaccination Patterns in Pregnant Women During the 2009 H1N1 Influenza Pandemic: A Population-based Study in Ontario, Canada - Liu, Ning (Can J Public Health, 2012)
OBJECTIVES: Influenza vaccination rate among pregnant women has typically been low, and there is little population-based information on predictors of vaccination uptake within this group. This study aimed to evaluate the rate of influenza vaccination in pregnant women during the 2009 H1N1 influenza pandemic and explore predictors associated with receiving vaccination during pregnancy. METHODS: We conducted a retrospective population-based cohort analysis involving women who gave birth in an Ontario hospital between November 2, 2009 and April 30, 2010. Rates of influenza vaccination were calculated according to maternal, obstetrical, behavioural and neighbourhood characteristics. Women who received influenza vaccination during pregnancy were compared with women who were not vaccinated using log-binomial regression to calculate adjusted relative risks (aRR) and 95% confidence intervals (CI). RESULTS: Among 56,654 women who gave birth in the study period, 42.6% had received influenza vaccination during pregnancy. Vaccine uptake was lower among women: of age <20 (aRR=0.80, 95% CI: 0.76–0.84), in lower socio-economic status (aRR=0.93, 95% CI: 0.90–0.96), without an antenatal care provider (aRR=0.72, 95% CI: 0.59–0.88), who did not initiate antenatal care in a timely manner (aRR=0.93, 95% CI: 0.91–0.96), who smoked during pregnancy (aRR=0.92, 95% CI: 0.89–0.95), and with a history of preterm birth (aRR=0.97, 95% CI:0.94-1.00). An increased vaccination rate was observed among women with medical co-morbidities (aRR=1.10, 95% CI: 1.07–1.13) and with family physicians (vs. obstetricians) as antenatal care providers (aRR=1.08, 95% CI: 1.06–1.10). CONCLUSION: We identified the prenatal population that may benefit from targeted public health intervention strategies to improve future vaccination rates for this priority vaccination group.